건강검진 수진 성인 남성에서 초음파검사를 이용한 갑상선결절의 유병률 - 김정현; Jung Hyun Kim; 박상준; Sang Jun Park; 김상억; Sang Eok Kim; 이광희; Kwang Hee Lee; 조일권; Il Kwon Cho; 장선익; Sun Ik Jang; et al. (Endocrinology and metabolism (Seoul), 2007)
연구배경: 갑상선결절은 촉지를 통해서 진단할 때 4~7%의 유병률을 보이는 흔한 질환이며 갑상선초음파검사를 시행하면 성인의 19~46%까지도 진단된다. 갑상선결절은 여성에서 4배 정도 유병률이 더 높으나 남성에서 여성보다 악성결절의 빈도가 높다. 저자들은 건진 센터를 찾은 일반 남성을 대상으로 갑상선초음파검사를 시행하여 갑상선결절의 유병률을 연구하였다. 방법: 1년간 본원 건진 센터를 방문했던 30세 이상의 성인 일반 남성 중 과거력상 갑상선 수술을 받았거나 갑상선질환으로 치료 중이거나 추적관찰 중인 경우를 제외한 1,081명을 대상으로 갑상선초음파를 실시하여 갑상선결절을 진단하고 필요시 미세침흡인세포검사를 시행하였다. 결과: 1,081명 중 152명에서 갑상선결절이 진단되어 14.1%의 유병률을 보였으며 높은 연령 군에서 결절의 빈도가 증가하였다(30~49세 12.3%, 50세 이상 17.2%)(P = 0.026). 결절의 크기가 5 mm 이상의 수진자 중 53명이 미세침흡인세포검사를 시행 받았으며 6명이 악성으로 진단되어 수술을 통해 확진하였다. 결론: 건진 센터를 방문한 일반 성인 남성을 대상으로 갑상선초음파검사로 진단한 갑상선결절의 유병률은 14.1%였으며 높은 연령군에서 유병률이 증가하였다. Background: Thyroid nodules are a common disease in clinical practice. The prevalence of thyroid nodules has recently been increased by according to the development of thyroid ultrasonography. Thyroid nodules are more commonly found in women, but the potential for malignant nodules is much higher in men. So, we aimed to focus on the prevalence of thyroid nodules in the adult male population. Methods: We studied men over the age of 30 who visited our health care center for routine health check-ups from January, 2005 to December, 2005. After excluding the patients with previous thyroid disorders, 1081 men were selected to undergo thyroid ultrasonography for detecting the presence of thyroid nodules. If nodules were found, then their size and numbers were recorded. These data were then correlated with the age of the patients. If needed, ultrasound-guided fine needle aspiration was performed. Results: Among the 1,081 subjects, thyroid nodules were detected in 152 (14.1%) with its prevalence increasing with the increasing age of the patients (age 30 to 49: 12.3%, over 50: 17.2%, P = 0.026). Among these study subjects, nodules larger than 5 mm in size were detected in 99 patients and fine needle aspirations were performed on 53 of these patients. Six patients were diagnosed with papillary carcinoma. Conclusion: The prevalence of thyroid nodules in the male population was 14.1%, with an increasing prevalence in the over 50 age group. (J Kor Endocrine Soc 22:112~117, 2007)